Revised Statutes of the State of Arkansas, Adopted at the October Session of the General Assembly of Said State, A.D. 1837, in the Year of Our Independence the Sixty second, and of the State of Second Year Page 587 § 18 - (:unkn) unknown (General Publisher, 1838)
Provided that every gun, rifle, weapon of any kind, ammunition found in the possession of any "free negro or mulatto" not having a license may be seized and violators fined not exceeding twenty dollars.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES